Smart green energy production - Vasant, Pandian 1961-; Weber, Gerhard-Wilhelm 1960-; Pančenko, Vladislav Ja. 20 Jht; Thomas, J. Joshua 1973- (De Gruyter, 2024)
This book discusses how intelligent algorithms and smart performance measurement approaches can be applied to the production of green energy and the management of carbon dioxyde emissions. It provides insights into the sustainable computational strategies to face problems through the utilization of techniques such as smart hybrid quantum computing, swarm intelligence, cloud computing, and optimization.
Keywords: Energy Harvesting; Intelligentes Stromnetz; Erneuerbare Energien; Algorithmus